2022
DOI: 10.1001/jamanetworkopen.2022.8573
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Vaccination Rates Among People With a New Diagnosis of HIV Infection in the US

Abstract: Key Points Question How many people with a new diagnosis of HIV infection—who are at increased risk of meningococcal disease—receive the recommended meningococcal A, C, W, Y (MenACWY) vaccination in the US? Findings This cohort study of 1208 vaccine-eligible individuals found that, 2 years after a diagnosis of HIV infection, 16.3% were estimated to have received 1 or more doses of the MenACWY vaccine. Uptake was higher among those who received pneumococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Despite these limitations, this study adds to the literature by providing an analysis of large numbers of adults in the US. Claims data are utilized often in vaccination administration studies, and the longitudinal information with dates of health care utilization allowed us to identify the exact timing of HPV vaccine administration and avoid biases related to self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, this study adds to the literature by providing an analysis of large numbers of adults in the US. Claims data are utilized often in vaccination administration studies, and the longitudinal information with dates of health care utilization allowed us to identify the exact timing of HPV vaccine administration and avoid biases related to self-report.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of LGBT inclusivity training for healthcare providers may help to encourage such disclosure, given this study and others [ 30 , 31 ] have identified a lack of LGBT cultural competency in the Inland Empire region. Healthcare provider education focused on vaccine recommendations for MSM will likely also be important for encouraging providers to discuss HPV and meningococcal vaccines with their eligible patients [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For individuals newly diagnosed with HIV, in a cohort study using US commercial claims, only 16.3% of individuals eligible for vaccination received a first dose of the MenACWY vaccine in the 2 years after an HIV diagnosis [ 15 ]. Also, among those individuals who received a first dose and had at least 1 year of continuous enrollment after the first dose, only 66.2% received a second dose within 1 year of the first dose [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We know the majority of vaccinations occur in a medical setting, where notable differences exist between provider types regarding the frequency of immunizing individuals at increased risk [ 13 15 ]. Therefore, medical education for healthcare providers and patients needs to be tailored to particular provider situations.…”
Section: Discussionmentioning
confidence: 99%